The effect of instructional leadership on student’s active and learning outcomes - Yuliana Pebristofora Marni Mala; Erny Roesminingsih; Yatim Riyanto (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2021)
Instructional leadership is strategically used to improve the quality of learning. This leadership style is leadership oriented to improve the quality of learning. Instructional leadership policy becomes the parameter of the school in improving the quality of learners' learning outcomes. The purpose of the study was: to know and analyze the influence of instructional leadership models on improving learning activity on student learning outcomes. This research uses the quantitative research method. Data collection using research instruments by disseminating questionnaires using google form. The results of this study are: (1) there is an influence of the instructional leadership model on improving the activeness of learners' learning, (2) there is an influence of the instructional leadership model on learners' learning outcomes, and (3) there is an influence of instructional leadership on improving the activeness of learning and learning outcomes of learners. It can be concluded that instructional leadership is effective in improving the quality of learning.